Workshop Pendampingan Pembuatan Media Pembelajaran Online Diera Pandemi Covid-19 Melalui PPT Termodifikasi - Siti Anisatur Rofiqah; Effendi Effendi; Dwi Andriani; M.Iqbal Mustofa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2022)
This service is motivated by the presence of a coronavirus disease that has been determined by the World Health Organization (WHO) as a pandemic condition with a massive level of ability to spread the virus to the entire world population, including Indonesia. Efforts to control and prevent the transmission of the corona virus are carried out by interacting and maintaining physical distance from others. These policies have an impact on all aspects of life, including the learning process of students at school. The biggest problem related to the bold learning process occurs in educators in kindergarten and elementary school in Simpang sub-district. The educators have difficulty in the bold learning process because of the lack of ability in the IT field. Although the average educator has a computer, but they are not able to operate it first for the learning process boldly. They only give assignments directly to students without any learning process. This has an impact on the ability and motivation of students in learning. We try to provide training and assistance in the use of modified Powerpoint media to overcome these problems with the target being the teacher's ability to use Modified Powerpoint so that the learning process is effective, innovative and fun for students.